2011
DOI: 10.1097/sap.0b013e3181edafdb
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Thigh Free Flap With Flow-Through Vascular Pedicle

Abstract: The lateral thigh flap based on the second and third perforator of profunda femoris vessel has not become very popular. We describe a technique of flow-through pedicle for this flap. The flow-through technique makes this flap very simple to transfer. The flap was used successfully in 6 cases for reconstruction for defects in the leg and forearm. The flow-through pedicle is ideal for lower limb reconstruction. The anastomosis becomes very easy and safe, even if the recipient vessels are deep in the intermuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…1417 In contrast, we used flow-through arterial anastomosis in this study to improve the patency rate and to stabilize the circulation of the flap, even when reconstructing recipient-artery continuity was unnecessary. We have previously demonstrated that flow-through arterial anastomosis has a higher patency rate than end-to-end and end-to-side anastomoses and increases the flow rate through the anastomotic site.…”
Section: Discussionmentioning
confidence: 99%
“…1417 In contrast, we used flow-through arterial anastomosis in this study to improve the patency rate and to stabilize the circulation of the flap, even when reconstructing recipient-artery continuity was unnecessary. We have previously demonstrated that flow-through arterial anastomosis has a higher patency rate than end-to-end and end-to-side anastomoses and increases the flow rate through the anastomotic site.…”
Section: Discussionmentioning
confidence: 99%
“…The flow-through flap is potentially the best choice in these situations, as it can simultaneously provide arterial reconstruction and soft-tissue coverage. [7][8][9][10][11][12][13][14][15][16] In our series, two flow-through ALTP flaps were used for simultaneous soft-tissue and vascular gap reconstruction (cases 2 and 3), and the flaps and distal limbs both survived postoperatively. In this situation, the pedicle of the flow-through flap must be interposed between two ends of the recipient vessel to bridge the vascular gap.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the severed phalanx can be well supplied by this flap in a flowthrough manner. 25 This island flap is especially suitable for the restoration of blood circulation in thumbs with proximal digital artery defects. In addition, this flap can cover softtissue defects.…”
Section: Discussionmentioning
confidence: 99%